2015
DOI: 10.1002/jbmr.2503
|View full text |Cite
|
Sign up to set email alerts
|

Mst2 Controls Bone Homeostasis by Regulating Osteoclast and Osteoblast Differentiation

Abstract: Mammalian sterile 20-like kinase 2 (Mst2) plays a central role in the Hippo pathway, controlling cell proliferation, differentiation, and apoptosis during development. However, the roles of Mst2 in osteoclast and osteoblast development are largely unknown. Here, we demonstrate that mice deficient in Mst2 exhibit osteoporotic phenotypes with increased numbers of osteoclasts and decreased numbers of osteoblasts as shown by micro-computed tomography (mCT) and histomorphometric analyses. Osteoclast precursors lack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…Recent work examining osteoclast-osteoblast differentiation has suggested that Hippo pathway kinases, such as Mst2, may affect the NF-κB pathway through phosphorylation of IkB proteins, thereby promoting nuclear translocation of NF-κB transcription factors (Lee et al, 2015). TAZ was found to be a direct target of NF-κB transcription factors and its expression is regulated via NF-κB signaling (Cho et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work examining osteoclast-osteoblast differentiation has suggested that Hippo pathway kinases, such as Mst2, may affect the NF-κB pathway through phosphorylation of IkB proteins, thereby promoting nuclear translocation of NF-κB transcription factors (Lee et al, 2015). TAZ was found to be a direct target of NF-κB transcription factors and its expression is regulated via NF-κB signaling (Cho et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…During the differentiation of osteoclasts from hematopoietic precursors, the monocytic cells must migrate and fuse together to form multinucleated mature osteoclasts [4]. Convincing evidence indicates that osteoclasts exert a critical role in maintaining bone homeostasis by replacing old bones with new bones through coordinating with osteoblasts [5,6]. Therefore, understanding the underlying mechanism involved in osteoclast differentiation and activation processes is urgently needed for the treatment of osteopenic diseases.…”
Section: Introductionmentioning
confidence: 98%
“…These results suggest a critical role of Hippo pathway proteins MST1/2 in osteoclast differentiation. Similarly, previous observation has also shown that MST2 KD could increase osteoclast differentiation [20]. However, as MST1 showed a more prominent change than MST2 in our system, we evaluated the Hippo pathway with osteoclast differentiation through MST1.…”
Section: Hippo Pathway Is Involved In Osteoclast Differentiationmentioning
confidence: 55%